Two-sample Mendelian randomization to study the causal association between gut microbiota and atherosclerosis - Jiang, Shijiu; Yu, Cheng; Lv, Bingjie; He, Shaolin; Zheng, Yuqi; Yang, Wenling; Wang, Boyuan; Li, Dazhu; Lin, Jibin (Frontiers in Immunology, 2024)
According to some recent observational studies, the gut microbiota influences atherosclerosis via the gut microbiota-artery axis. However, the causal role of the gut microbiota in atherosclerosis remains unclear.Therefore, we used a Mendelian randomization (MR) strategy to try to dissect this causative link.The biggest known genome-wide association study (GWAS) (n = 13,266) from the MiBioGen collaboration was used to provide summary data on the gut microbiota for a two-sample MR research. Data on atherosclerosis were obtained from publicly available GWAS data from the FinnGen consortium, including cerebral atherosclerosis (104 cases and 218,688 controls), coronary atherosclerosis (23,363 cases and 187,840 controls), and peripheral atherosclerosis (6631 cases and 162,201 controls). The causal link between gut microbiota and atherosclerosis was investigated using inverse variance weighting, MR-Egger, weighted median, weighted mode, and simple mode approaches, among which inverse variance weighting was the main research method. Cochran's Q statistic was used to quantify the heterogeneity of instrumental variables (IVs), and the MR Egger intercept test was used to assess the pleiotropy of IVs.Inverse-variance-weighted (IVW) estimation showed that genus Ruminiclostridium 9 had a protective influence on cerebral atherosclerosis (OR = 0.10, 95% CI: 0.01-0.67, P = 0.018), while family Rikenellaceae